PENDIDIKAN KEWARGANEGARAAN SEBAGAI PRAKTIK KETERLIBATAN POLITIK DI INDONESIA - Mujianti Rahayu, bening; Yuyu Yuhana; Maman Fathurrohman (Universitas Al-Qolam Malang, 2024)
The purpose of this research is to find out the extent of citizen involvement in political activities and socialisation in everyday life and how to implement it. This article uses a literature study type of research where previous research that has been collected will be compiled, analysed and then concluded so as to get observations about the material under study. The conclusion of this research includes all Indonesian citizens who participate in political practices and socialisation in every daily activity, one of which is by using a case-based learning system, and how teenagers use social media responsibly, then ordinary people who involve themselves with democracy through voting and expressing their opinions wisely in accordance with the teachings of Civic Education and Pancasila.